THU0544 MULTIMODAL PHOTOACOUSTIC/ULTRASONIC IMAGING SYSTEM: A NEW IMAGING METHOD FOR EVALUATING RA. (2nd June 2020) - Zhao, C.; Wang, Q.; Tao, X.; Yu, C.; Liu, S.; LI, M.; Tian, X.; Qi, Z.; LI, J.; Yang, F.; Zhu, L.; Zeng, X.; et al.
Abstract : Background: Photoacoustic imaging (PAI), a new imaging technique which can be integrating with ultrasound (US) imaging, has shown potential in visualizing small joints. We have developed a multimodal photoacoustic/ultrasound (PA/US) imaging system, equipped with a handheld probe, which can provide dual-wavelength PA/US imaging to identify the micro-vessels of the inflamed articular regions and measure the oxygenation level of human inflamed synovium. Objectives: To validate the potential value for RA of the imaging system. Methods: A total of 32 RA patients received PA/US examination on seven small joints (MCP2, MCP3, PIP2, PIP3, MTP2, MTP5, and wrist of the clinically dominant side). The 0-3 score was used to semi-quantify the PA and PD signals of the inflammatory articular lesions, and the sums of PA and PD scores (PA-sum and PD-sum) were utilized. The relative oxygen saturation (SO2) values of the inflamed regions were measured by calculating the ratio of PA signals at the wavelength of 750nm and 830nm. All the patients were classified to 3 PA+SO2 patterns (Pattern 1: no or minimal PA signals; Pattern 2: evident PA signals and hyperoxia; Pattern 3: evident PA signals and hypoxia). The correlations between imaging scores and laboratory data, as well as clinical scoring systems were assessed. Results: A total of 32 patients of RA were recruited aged from 25-71 years-old were examined. PD-sum had moderate correlation with the clinical scores (r=0.529, 0.546, 0.490, 0.493 for DAS28ESR, DAS28CRP, SDAI, CDAI), moderate correlations with TJC (r=0.575) and SJC (r=0.491), fair correlation with VAS (r=0.239), poor correlation with PGA (r=0.153), and moderate correlation with EGA (r=0.457). The PA-sum had substantial correlations with the clinical scores (r= 0.699, 0.746, 0.723, 0.736 for DAS28ESR, DAS28CRP, SDAI, CDAI), substantial correlations with TJC (r=0.787) and SJC (r=0.694), moderate correlations with VAS (r=0.544) and PGA (r=0.529), and substantial correlation with EGA (r=0.708). Ten patients were classified as Pattern 1, 12 as Pattern 2, 9 as Pattern 3. The PA+ SO2 patterns presented substantial correlations with the clinical scores (DAS28ESR r=0.690, DAS28CRP r=0.782, SDAI r=0.805, CDAI r=0.799, SJC r=647, TJC r=0.676, respectively), substantial correlation with VAS (r=0.714), and moderate correlation with PGA (r=0.476) and EGA (r=0.502). Significant differences between those who were classified as hypoxia and hyperoxia with evident PA signals, were detected in VAS (p=0.020) and PGA (p=0.026). Conclusion: The PA-sum scores and the PA+SO2 patterns can be utilized as objective imaging parameters reflecting the disease activity of RA. PAI may serve as a supplement to conventional US examinations for RA patients. References: [1]Backhaus, M., et al., Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot project. Arthritis Rheum, 2009. 61(9): p. 1194-201. [2]Colebatch, A.N., et al., EULAR recommendations for the use of imaging of the joints in the clinical management of rheumatoid arthritis. Ann Rheum Dis, 2013. 72(6): p. 804-14. Disclosure of Interests: Chenyang Zhao: None declared, Qian Wang: None declared, Xixi Tao: None declared, Chen Yu: None declared, Sirui Liu: None declared, Mengtao Li: None declared, Xinping Tian: None declared, Zhenhong Qi: None declared, Jianchu Li: None declared, Fang Yang: None declared, Lei Zhu: None declared, Xiaofeng Zeng Consultant of: MSD Pharmaceuticals, Meng Yang: None declared, Yuxin Jiang: None declared